Evaluation of immunochromatographic tests for detection of a wide variety of group a rotavirus genotypes and adenovirus - Pattara Khamrin (2020)
© 2019 Verlag Klinisches Labor GmbH. All rights reserved. Background: Viral gastroenteritis is one of the most common illnesses in humans worldwide, and different viral agents have been shown to be associated with the disease. Among these, rotaviruses and adenoviruses are the responsible causative agents of acute gastroenteritis and causing numerous outbreaks. Therefore, a simple and rapid diagnostic tool, such as an immunochromatographic (IC) test, is required for rapid diagnosis, especially during an outbreak of these pathogens. Methods: The efficiency of two commercial IC kits were evaluated for simultaneous detections of rotavirus and adenovirus in clinical stool specimens by a single test kit. Results: The data demonstrated that both IC test kits could detect either adenovirus or rotavirus positive alone, as well as mixed infections of both viruses in a single stool specimen. In addition, a wide variety of rotavirus genotypes, including G1-P[8]-I1, G2-P[4]-I2, G3-P[8]-I2, G8-P[8]-I2, and G9-P[8]-I1 could be detected by both IC kits. The detection limit of the kits for the detection of rotavirus and adenovirus were comparable to those of real-time PCR at 105 copies/mL. Conclusions: These two IC test kits could be used as an alternative choice for rapid screening of rotavirus and adenovirus in the stool specimens, especially during the seasonal outbreak of acute gastroenteritis.